Strategi Pengembangan Bisnis Jasa Makeup Artist Dengan Pendekatan Business Model Canvas : Studi Pada Erha Makeup Artist Bandung - Rahayu, Kartini; Herlinawati, Erna (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
MSMEs Contribute to empoyment absorption, economic growth, and the distribution of development outcomes. The increasing number of MSMEs in Indonesia is partly evident in the growth of the Makeup Artist service sector. The rising enthusiasm among the public to estabilish businesses in this sector has led to intensified competition faced by Erha Makeup. To formulate business development strategies for Erha Makeup, this study employs a qualitative descriptive method, processing primary data through interviews with the owner of Erha Makeup and secondary data through relevant literatur. Additionally, SWOT analysis is used to evaluate Strengths, Weaknesses. Opportunities, and Threats, wich are then linked to the Business Model Canvas (BMC) to provide a comperhensive strategic overview of essential business competents. The result of study indicate that Erha Makeup has fulfilled all elements of the Business Model Canvas required to operate its business. However, there are still aspects that need improvement as outlined in the SWOT analysis of Erha makeup, primary strengths include professional services, high-quality products, a deep understanding of customers spesific need, and the use of social media marketinf to reach a wider market. The main Weaknesses are its reliance on seasonal demand and unstructured capital management. Significant opportunities lie in building trust through social media, while the threats stem from intense competition and the need for continuous innovation. The proposed strategies include diversifying service, fostering sustainable innovation, enhancing branding by optimizing social media, and offering loyalty or referral programs to streng then customer relationships.